Corrigenda "Samir Amin (1931-2018) y el desarrollo desigual" - Domínguez-Martín, Rafael (Iberoamerican Journal of Development Studies, 2023)
Corrigenda in the article "Samir Amin (1931-2018) y el desarrollo desigual", published in the Volume 8, issue 2. The online version of the original article can be found at: http://ried.unizar.es/index.php/revista/article/viewFile/472/pdf